Violência entre parceiras íntimas: caracterização do fenômeno e avaliação da rede de apoio das vítimas - Furukawa, Letícia Yuki de Araujo (2022)
Intimate Partner Violence (IPV) is recurrent in the daily lives of many Brazilian women. Despite the recognition of the impacts of IPV, as well as the existence of homosexual relationships between women in numerous cultures, there are few studies that have focused on the experiences of violence experienced in these relationships, especially in the national context. The absence of investigations focused on this segment hides the epidemiological data and mask this harmful reality. It was hypothesized that lesbians who do not have the perception of support from social support are more exposed to IPV, as well as having more difficulties in breaking up with the aggressor partner. Based on these prerogatives, the objective of this research was to characterize IPV, more specifically in women's homosexual relationships, as well as to analyze possible associations between Perceived Social Support (PSS). This is a quantitative investigation, with a cross-sectional design, organized into three complementary studies that were presented in the form of articles. A total of 1057 Brazilian lesbian women, aged between 18 and 58 years old, participated in the investigation. Data collection was online and the following instruments were used: i) Brazil Socioeconomic Classification Criteria; ii) Revised Tactical Conflict Scale (CTS-2); iii) Perceived Social Support Scale (adult version) (EPSUS-A). Article 1 aimed to verify the association between IPV and PSS, based on the socioeconomic, ethnic and educational classification of Brazilian lesbian women. Data were analyzed using Pearson's correlation coefficient, which did not differ significantly in relation to violence data, with only differences in relation to PSS being observed. The study, despite its limitations, suggests that violence in women's homosexual relationships occurs in all social strata, regardless of ethnicity and level and education. Articles 2 and 3 are closely related as the sample was split so that Latent Class Analysis (LCA) could be conducted. In Article 2, based on an exploratory model, the objective was to characterize the manifestation of violence in women's homosexual relationships (n = 634) based on its typology and frequency, and to analyze the possible associations between violence and the perception of social support. Four significantly different classes were identified in terms of patterns of violence suffered and perceived social support. The findings reinforced that the relationship between partner violence and social support is a heterogeneous phenomenon, whose variables are not always directly related. Subsequently, in Article 3, the confirmatory analysis was performed. The sample consisted of 423 lesbian women and the number of classes obtained in the present study, through the LCA, confirmed the number of classes in the exploratory study. However, the results of this investigation suggested that the perception of social support can reduce the prevalence of violence in the relationship of only a part of the participating women. Other psychological and social variables should be included in studies of this size to detect other dimensions that are directly associated with the reduction or perpetuation of indicators of violence in women's homosexual relationships. It is hoped that this investigation will contribute to the unveiling of obscured issues regarding the manifestation of violence between intimate partners, as well as subsidize consistent reflections on the role of the support network in the rupture of violence in these relationships.